Preface - Verster, Pieter (Acta Theologica, 2012)
From text: A Second International Conference of Missiology was presented at the Faculty of Theology by the Department of Missiology on the theme: “Good news for the poor and the sick” on 13 May 2011. International speakers, namely Prof. Joachim Kügler (Germany), Prof. Nalini Arles (India) and Prof. Lovemore Togarasei (Botswana) presented papers. The aim of the Conference was to engage in academic discussion on the way and means to be involved in the serious challenges posed by poverty and the HIV/AIDS epidemic. From different perspectives solutions were sought and possible biblical, theological and developmental suggestions to get involved and to bring hope were discussed.